Beta Blocker Therapy in Heart Failure Patients with Active Cocaine Use: A Systematic Review - Baldeep K. Mann; Janpreet S. Bhandohal; Mohammad Saeed; Gerald Pekler (Cardiology Research and Practice)
Background. Cocaine use is associated with multiple cardiovascular complications including heart failure. The use of different types of beta blockers in heart failure patients with active cocaine use is still a matter of debate. In this review, our objective is to systematically review the available literature regarding the use of beta blockers in the treatment of heart failure patients with concurrent cocaine use. Methods. PubMed, EMBASE, Web of Science, and Clinical Trials.gov were searched from inception to March 2019 using the Medical Subject Headings (MeSH) terms “cocaine”, “heart failure”, “beta blocker,” and “cardiomyopathy”. Only studies containing the outcomes of heart failure patients with active cocaine use who were treated with beta blockers were included. Results. The search resulted in 2072 articles out of which 12 were finally included in the review. A total number of participants were 1994 with a median sample size of 111. Most of the studies were retrospective in nature with Oxford Centre for Evidence-Based Medicine (OCEBM) Levels of Evidence from 3 to 5. The main primary outcomes included readmission rates, mortality, left ventricular ejection fraction (LVEF) improvement, New York Heart Association (NYHA) functional class, and major adverse cardiovascular events (MACEs). In the studies analyzed, beta blockers were found to have either a beneficial or a neutral effect on primary outcomes in heart failure patients with active cocaine use. Conclusion. The use of beta blocker therapy appears to be safe and beneficial in heart failure patients with active cocaine use, although the evidence is not robust. Furthermore, large-scale studies are required to confirm this finding.